PENERAPAN GAME THEORY DALAM PEMASARAN FRAKSI SIRTU PADA PT X DAN PT Y - Arif Setiawan; Djusman Bin Aziz; Indra Birawaputra; Bambang Triyanto; Ismiyati (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2022)
The increasing demand for sand and stone materials has resulted in competitions between mining companies in order to meet the need of the material for construction activities, from which it results in conflicts between two parties, two people, or groups of people. Part of the mathematical programming technique used to analyze the decision-making process of competition between two or more parties is Game Theory. The application of game theory is to produce the best strategy that will be used by a company to optimize the marketing of gravel fraction. Instruments or tools used in the research is a questionnaire that includes improving product quality, affordable pricing, improving service quality, establishing an effective corporate work process, and determining the place of inventory. The result is arranged in the form of a payoff matrix and analyzed using the Game Theory, that indicates the competition between PT X and PT Y. The analysis results show that the implementation of those strategies is the best way that can optimize marketing of gravel fraction, so that it can improve the position of profit or loss got saddle point from competition between PT X and PT Y, which is 11. The results also confirm the increase of profit of PT X, from 10 to 11 by applying effective work processes (probability 5:1). In addition, the loss of PT Y could decrease from 12 to 11 by applying strategies to improve the product quality of gravel fraction and determining the stock of the fraction (probability 1:1).